Rethinking religion and world affairs - Shah, Timothy Samuel (Oxford University Press, 2011)
In recent years, the role of religion in the study and conduct of international affairs has become increasingly important. The essays in this volume seek to question and remedy the problematic neglect of religion in extant scholarship, grappling with puzzles, issues, and questions concerning religion and world affairs in six major areas. Contributors critically revisit the "secularization thesis," which proclaimed the steady erosion of religion's public presence as an effect of modernization; explore the relationship between religion, democracy, and the juridico-political discourse o